Comparative Archetypal Study on Ragnarok and Christianity Apocalypse - Wijianto, Agung (Jurnal Ilmiah Mahasiswa FIB, 2014)
Wijianto, Agung. 2012.  Comparative Archetypal Study on Ragnarok and Christianity Apocalypse.  Study Program of English,  Faculty of Cultural Studies University of Brawijaya. Supervisor:  Yusri Fajar;Co-supervisor: Scarletina VidyayaniKeywords:  Ragnarok, Apocalypse, archetypes, motifs.The stories about the end of the world always attract human interests. This is proven by the fact there are a lot of works that illustrate the scenarios of the End of the World. These works may be found times to times either from myths, cultures, or simply fictions. Among of all of those works, Ragnarok from Norse myth and Apocalypse from Christianity are possibly the most intriguing stories. It will be constructive to compare these two stories by using the means of archetypes. This archetypal comparison will lead to the understanding of the deep implication that both stories correspond. Archetypal approach is an approach  that studies the universal symbols called archetypes and plots called motifs contained within the story. These archetypes will serve greatly as the tool of analysis since the universality of these symbols can be applied to both works. The analysis of the archetypes will contain two categories which are the motifs and the archetypal characters.  Throughout the study, it has been found that despite the cultural and background differences of Ragnarok and Apocalypse, these two works contain universal plots and universal characters in them. It cannot be denied there are so many similarities on the terms of the archetypes. Both of the works use same motifs underlying in the plot. The same implications of the portrayal of the villain also prove to be remarkable. Ragnarok and Apocalypse, two works of different origins and cultures, contained so many similarities judging from the archetypal point of view. To a certain degree, it is recommended to further study these two works using historical approach. The comparison of how historical background affects the content of these two stories will be useful for a literary study.